2015
DOI: 10.1371/journal.pone.0121589
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Mediated Gene Expression Depends on RhoA and Rac1 Signaling in Proximal Tubular Epithelial Cells

Abstract: Morphological alterations of cells can lead to modulation of gene expression. An essential link is the MKL1-dependent activation of serum response factor (SRF), which translates changes in the ratio of G- and F-actin into mRNA transcription. SRF activation is only partially characterized in non-transformed epithelial cells. Therefore, the impact of GTPases of the Rho family and changes in F-actin structures were analyzed in renal proximal tubular epithelial cells. Activation of SRF signaling was compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Induction of CTGF by EGTA was dependent on signaling pathways which have earlier been described to regulate CTGF expression in epithelial cells, e.g. ERK and RhoA [19][20][21][22]. Inhibition of ERK1/2 by U0126 (0.5 M) abrogated CTGF induction.…”
Section: Egta-induced Ctgf Expression Is Related To Erk Activation Anmentioning
confidence: 74%
See 2 more Smart Citations
“…Induction of CTGF by EGTA was dependent on signaling pathways which have earlier been described to regulate CTGF expression in epithelial cells, e.g. ERK and RhoA [19][20][21][22]. Inhibition of ERK1/2 by U0126 (0.5 M) abrogated CTGF induction.…”
Section: Egta-induced Ctgf Expression Is Related To Erk Activation Anmentioning
confidence: 74%
“…CTGF expression is regulated via RhoA/Rho kinase signaling [19,20,[23][24][25]. This pathway also played a role in the EGTA-mediated induction of CTGF which was sensitive to treatment with the inhibitor of Rho kinases, H1152 (Fig.…”
Section: Egta-induced Ctgf Expression Is Related To Erk Activation Anmentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis of actin polymerization rate and expression revealed that both are concomitantly reduced by GPER/RhoA signaling in fibroblasts, pointing toward an unidentified negative feedback pathway. Regulation of gene expression by RhoAmediated actin polymerization has been previously described in proximal tubular epithelial cells through the myocardin-related transcription factor A/serum response factor (MRTF-A/SRF) axis (Giehl et al, 2015). MRTF-A is normally inactive in the cytoplasm through binding to G-actin monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of CTGF is dependent, in part, on the actin cytoskeleton; this has been in shown in primary human tubular epithelial cells (Kroening et al, 2009) and other cell types (Sakai et al, 2013;Chowdhury and Chagour, 2004). More specifically, CTGF regulation in a human proximal tubular cell line (HKC-8) is dependent upon the MAL/myocardin related transcription factor A (MRTF; megakaryoblastic leukemia 1)/serum response factor pathway downstream of RhoA (Giehl, et al, 2015). This pathway is perhaps the prototypic pathway regulated by the cytoskeleton as monomeric actin regulates gene expression through serum response factor by inhibition of MAL/MRTF (Leitner et al, 2011).…”
Section: A Link Between Disruption Of the Actin Cytoskeleton And Fibrmentioning
confidence: 99%